2018
DOI: 10.1016/j.landurbplan.2018.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Towards an operational methodology to optimize ecosystem services provided by urban soils

Abstract: et al.. Towards an operational methodology to optimize ecosystem services provided by urban soils. Landscape and Urban Planning, Elsevier, 2018, 176, pp.Urban soils need to be taken into account by city managers to tackle the major urban environmental issues. As other soils in forest or agricultural environments, urban soils provide a wide range of ecosystem services. However, their contribution remains poorly assessed up to now, and as a result there is a strong lack of consideration by urban planning of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 51 publications
1
26
0
2
Order By: Relevance
“…Therefore, the use of simple concepts is an acceptable alternative. Blanchart et al (2018) suggested (i) using a restricted number of indicators (set of parameters resulting from measurements and computations), (ii) using a descriptive integrative list of indicators expressing the functioning of soil, (iii) integrating the vertical and horizontal heterogeneities of urban soils, and (iv) using an adequate ranking system for each indicator. According to these suggestions, we use soil fertility as a simplification to evaluate urban soil quality.…”
Section: N4c Project Methodologymentioning
confidence: 99%
“…Therefore, the use of simple concepts is an acceptable alternative. Blanchart et al (2018) suggested (i) using a restricted number of indicators (set of parameters resulting from measurements and computations), (ii) using a descriptive integrative list of indicators expressing the functioning of soil, (iii) integrating the vertical and horizontal heterogeneities of urban soils, and (iv) using an adequate ranking system for each indicator. According to these suggestions, we use soil fertility as a simplification to evaluate urban soil quality.…”
Section: N4c Project Methodologymentioning
confidence: 99%
“…In concept, the valuation of Earth's critical zone services arising from stocks and flows occurring through the full vertical extent of the defined physical system offers the potential for a more complete understanding of its status and role as human habitat in supporting economic development, governing the impact of human activity on the Earth system, and improving human well-being [3]. This awareness offers potential to help decision-makers in the commercial and policy arenas seek reasonable methods of resources allocation and ecosystem management for the mitigation of the major environmental risks and for the development of a sustainable and resilient society by more optimal utilization of the full range of Earth's critical zone services [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…EOC is very sensitive to the external environment, and many studies have reported on the factors affecting the distribution of EOC, including intrinsic factors such as climate, topography, and soil groups and extrinsic factors such as land‐use patterns and farming practices (Chang et al, ; Li et al, ; Li et al, ; Li et al, ; Qi et al, ; Rabbi et al, ). With the increasing influence of human activity on global carbon transformation, external factors have received growing attention (Anne et al, ; Hobley, Baldock, Hua, & Wilson, ; Ye et al, ; Zhang et al, ), and the complexities and dynamics of subsurface EOC have been observed globally due to rapid urbanization and persistent human disturbance. On one hand, with rapid population growth and rapid economic development, greater demands for agricultural products and urban expansion (Bretzel et al, ; Liu & Guo, ; Ye et al, ) have resulted in improvements to the agricultural output efficiency and enhancement of the degree of agricultural intensification.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, with rapid population growth and rapid economic development, greater demands for agricultural products and urban expansion (Bretzel et al, ; Liu & Guo, ; Ye et al, ) have resulted in improvements to the agricultural output efficiency and enhancement of the degree of agricultural intensification. Meanwhile, with rapid urbanization, different urban radiation areas with different levels of socioeconomic factors, such as economic circles, urbanization rates (URs), population densities, and road densities, and land‐use factors, such as land‐use patterns and cultivated land pressure indices (Breure, Lijzen, & Maring, ; Hersperger et al, ), may gradually impact soil properties (Anne et al, ; Breure et al, ; Liu et al, ; Smidt, Tayyebi, Kendall, Pijanowski, & Hyndman, ; Sun et al, ). Although some studies have shown the impact of extrinsic factors such as land use and management and roads on soil properties in suburban areas (Li et al, ; Smidt et al, ; Stumpf et al, ; Ye et al, ), few studies have attempted to simultaneously link multiple environmental factors (internal factors and external factors) to the composition of EOC affected by rapid urbanization at the macro scale.…”
Section: Introductionmentioning
confidence: 99%